2005
DOI: 10.1002/eji.200425807
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses toPlasmodium vivax pre-erythrocytic stage antigens in naturally exposed Duffy-negative humans: a potential model for identification of liver-stage antigens

Abstract: Duffy antigen is the receptor used by Plasmodium vivax to invade erythrocytes. Consequently, individuals lacking Duffy antigen [Fy(-)] do not develop blood-stage infections. We hypothesized that naturally exposed Fy(-) humans may develop immune responses mainly to pre-erythrocytic stages and could be used to study acquired immunity to P. vivax and to identify liver-stage antigens. We report here that antibody and IFN-c responses to known sporozoite antigens were significantly induced by natural exposure in Fy(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Using mouse malaria model infections, it was observed that CD8 + T cells and protection against liver infection are induced by natural infections only when blood-stage development is inhibited by drug treatments, but not when blood-stage infections were fully developed [20][21][22]. Recently, it was found that in P. vivax endemic areas, individuals that do not develop blood stages because they do not have the Duffy antigen had significantly higher IFN-c responses to sporozoite antigens, suggesting again that blood-stage infections inhibit T cell responses to pre-erythrocytic stages [23].…”
Section: Introductionmentioning
confidence: 99%
“…Using mouse malaria model infections, it was observed that CD8 + T cells and protection against liver infection are induced by natural infections only when blood-stage development is inhibited by drug treatments, but not when blood-stage infections were fully developed [20][21][22]. Recently, it was found that in P. vivax endemic areas, individuals that do not develop blood stages because they do not have the Duffy antigen had significantly higher IFN-c responses to sporozoite antigens, suggesting again that blood-stage infections inhibit T cell responses to pre-erythrocytic stages [23].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, pooled synthetic peptides are used in IFN-γ (IFNγ) enzyme-linked immunosorbent spot (ELISPOT) assays to identify T-cell targets (29), but even with pooling strategies (30), these approaches require complex, expensive peptide libraries. In lieu of peptides, plasmidencoded parasite genes can be transfected into antigen-presenting cells (APCs) (31), but this approach is low throughput and difficult because of the A/T-richness of Plasmodial genes. Instead here, we used a minigene-based high-throughput screen (HTS) for CTLs (32) to study a library of Plasmodium yoelii-derived antigens in sporozoite-vaccinated mice.…”
mentioning
confidence: 99%
“…5,8 These donors have been shown to develop significantly fewer antibodies to blood-stages antigens compared with Fy+ donors. 46,47 To investigate the antibody responses induced by natural exposure to P. vivax infection, the protein arrays containing 91 P. vivax proteins were interrogated with 60 sera from P. vivax-exposed individuals and 7 control sera from unexposed individuals (Figure 1). The exposed donors were further subdivided into two groups according to their Fy genotype (Fy+ or Fy−).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that Fy− individuals exposed to P. vivax in Colombia responded predominantly to pre-erythrocytic antigens rather than erythrocytic antigens. 14 The lack of DARC on Fy− erythrocytes and the resulting prevention or reduction of blood-stage parasitemia may consequently reduce the frequency of exposure to erythrocytic parasites in the Fy− population compared with the Fy+ population. [14][15][16] Furthermore, it has been shown that, in both murine (P. yoelii) and human (P. falciparum) malaria, bloodstage infections suppress T-cell responses against liver-stage antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation